Stress Management and Employee Counselling: It’s Imperative to the Nigerian Public Service - Muhammad, , Hauwa A.; S. Y., Muhammad (Kashere Journal of Education, 2021)
The paper highlights the importance and the major causes of employee stress, and provides explanations on stress management and employee counselling as a major tool for managing stress in organizations. This work delves and relies heavily on secondary source of data. It also employs the Person Environment fit model theory in its explanation and analysis which believes that both external and internal causative factors are referred to as stressors, and the resulting state of the individual - poor physical health, job dissatisfaction, turn-over as stress. The model posits that for stress to be properly understood, it must be seen as an outcome of interaction of characteristics of both the focal individual [person, employee or worker] and his environment. Person-Environment Fit States Some of the stressors common to Nigerian public servants, include incessant power failure, bad roads, road congestions, environmental hazards among few. the paper concludes by Recommending for the establishment of counselling units in organizations, provision of infrastructure like good roads to reduce road congestions, provision of stable power supply, and payment of living wage